Analysis of Rejang Dance in Pedawa Village, Buleleng - Januar, Rizky (Bali Tourism Board, 2025)
This study explores the cultural and symbolic dimensions of the Rejang dance as practiced in Pedawa Village, Banjar District, Buleleng Regency, Bali. Drawing on a qualitative descriptive methodology, the research focuses on the interrelation between dance, costume, ritual, and community identity within the Bali Aga tradition. Data collection was conducted through in-depth interviews and participant observation during ceremonial performances. The findings highlight the Rejang dance as a sacred ritual (wali) performed exclusively by unmarried adolescent girls known as Daa. These dancers wear elaborate, multilayered costumes made from rare woven fabrics, with each component—such as the kain rembang, seropong headdress, and floral adornments—imbued with symbolic meaning. The choreography’s slow and deliberate movements are influenced by both the sacred nature of the ritual and the constraints of the ceremonial attire. The research reveals that participation in the dance is governed by a hereditary system rooted in lineage and ritual purity. The designation of Daa follows strict community rules, with each family allowed only one representative at a time. The performance of Rejang during ceremonies such as Saba Malunin is both a rite of passage and an expression of ancestral devotion. Additionally, the use of biodegradable ritual offerings reflects the community’s ecological awareness. Overall, the Rejang dance in Pedawa functions as a medium of intergenerational knowledge transmission, reinforcing cultural values, spiritual beliefs, and social cohesion. It exemplifies how dance, costume, and ritual intersect to sustain a distinct cultural identity within a rapidly changing world.